The Psychometric Properties of the Norwegian version of Children’s Sleep Habits Questionnaire (CSHQ) - Hysing, Mari; Sivertsen, Børge (PsykTestBarn, 2013)
Description: The Children’s Sleep Habits Questionnaire is a parent-reported questionnaire assessing sleep behavior and sleep problems in children. Literature search: A systematic literature search identified two Norwegian studies. Psychometrics: None of the included studies included norms or validity analysis. In one study, the test discriminated between a group of children with mental health problems and a control group. The reliability was generally good, but poor on the subscale assessing sleep-related breathing problems. Conclusion: Only one study of children with mental health problems was identified and thus the possibility of concluding on the psychometric properties is limited. Caution is advised when interpreting the results clinically. Population-based Norwegian studies assessing the psychometric properties are called for.